Menakar Kompetensi Dosen Pendidikan Agama Islam Di Era Society 5.0 - Nasution, Abdusima; Arsyad, Junaidi; Kurniawan, Syamsul (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Islamic Religious Education lecturers are required to be lecturers who always follow the flow of digital technology. Learning must be immediately abandoned towards conventional learning with digital society 5.0 nuances. Learning Islamic Religious Education by integrating technology and Islamic education has become an obligation to keep up with developments in educational technology. This preparation requires encouragement in managing materials, learning models and applications in an academic climate. This ability is intended so that lecturers are not left behind by students' abilities. Competencies that must be possessed in addition to mastery of technology are the competence of integrating Islamic values in technology-based learning, the competence of mastering curriculum development relevant to the era of society 5.0, the competence of academic guidance oriented to the era of society 5.0 and the competence of evaluating students' competence in using technology in learning, skills, critical , analytical and relevance of Islamic education values to the era of society 5.0.